Pengaruh Program Edukasi Manajemen Diabetes Melitus (Promedia) terhadap Parameter Metabolik pada Pasien Diabetes Melitus Tipe II di RSUD dr. Slamet Garut - Iin Patimah; Iwan Wahyudi; Susan Susyanti (Jurnal Medika Cendikia, 2017)
Diabetes mellitus is one of the chronic diseases with the incidence of disease is increasing from year to year. Without good management of diabetes mellitus may cause some complications that impact on the decrease of patient's life quality, therefore an effort is needed so that patients can manage the disease to avoid complications. One of the first steps in disease management is education. Promedia is one of the educational programs on DM disease management followed by regular follow-up through telenursing (follow up via phone). The purpose of this study was to see the effect of diabetes mellitus management education program (Promedia) on metabolic parameters in patients with type II DM who were outpatient in RSUD dr. Slamet Garut. Implementation in 4 months consists of educational phase (4 meetings) and followed follow up for 12 weeks through telenursing. Research design with quasi experiment with control group pre and posttest design; total sampling, parametric measurement data analysis using t test. The results of the measurement analysis in the intervention group were obtained BB (P value 0,00), systolic BP (P value 0.01), diastolic BP (P value 0.02), blood sugar level (P value 0,00), Cholesterol (P value 0.02), so it can be concluded there are significant differences between first and second measurement. Meanwhile, the results of the measurement analysis in the control group obtained BB (P value 0.08), Systolic BP (0.085), diastolic BP (P value 0.33), blood sugar level (P value 0.75), Cholesterol (P value 0.18), so it can be concluded there is no significant difference between first and second measurement. Based on the result of the research, it can be concluded that there is a significant influence between Diabetes Melitus Management Education Program (Promedia) on metabolic weight, blood pressure, blood sugar and cholesterol. From these results it is recommended to use Promedia as an integral part of the management diabetes mellitus handling of diabetes type II.